Todo por un sueño : nada ni nadie la detendrá... en su camino hacia el éxito - Sant, Gus Van; Kidman, Nicole, 1967- (Filmax, 2000)
Suzanne Stone is an aspiring TV personality who will do anything to be in the spotlight- including enlisting 3 teenagers to kill her husband.